2015
DOI: 10.18394/iid.90685
|View full text |Cite
|
Sign up to set email alerts
|

Yöneticilerin Algılanan Kültürel Zekâsı, Çalışanın Farklılık İklimi Algısı, Gelişime Açıklık ve Örgütsel Sinizm Etkileşimi Üzerine Turizm Sektöründe Bir Araştırma

Abstract: Bu araştırmanın amacı, yöneticilerin algılanan kültürel zekâsı, çalışanların farklılık iklimi algısı ve çalışanların deneyime açıklık özelliklerini araştırmak, olumsuz çalışan davranışı olarak adlandırılan sinisizm üzerindeki etkilerini açıklamak ve farklılıkların yönetiminin önemine değinmektir. Veriler, otellerde çalışan 160 kişiden anket yöntemiyle toplanmıştır. Anket formu, kültürel zekâ, örgütsel sinisizm, farklılık iklimi algısı ve deneyime açıklık ölçeği ile demografik soruları kapsamıştır. Değişkenler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Also, its relationship with premises such as personality traits (Ang, Van Dyne & Koh, 2006), cross-cultural experience and orientation (Crowne, 2008;Harrison, 2012;Li, Mobley & Kelly, 2013;Kurpis & Hunter, 2017;Pekerti & Arli, 2017;Schwarzenthal, Juang, Schachner, Van de Vijver & Handrick, 2017) and social intelligence (Depaula, Azzollini, Cosentino & Castillo, 2016) has been studied. According to the findings in the literature, it is shown that cultural intelligence increases the job satisfaction of employees in multinational organizations with cultural diversity and reduces their anxiety levels (Bücker, Furrer, Poutsma & Buyens, 2014;Telli & Zehir, 2016), burnout (Tay, Westman & Chia, 2008) and cynicism (Çalışkan, Ünal, Kalafatoğlu, Üçler & Akün, 2015). On the other hand, it has been observed that cultural intelligence positively affects team performance (Groves & Feyerherm, 2011) and increases both organizational commitment (Eskandarpur, Nazari, Vejdan & Tohidi, 2013) and job performance (Rose, Ramalu, Uli & Kumar, 2010: 76-85).…”
Section: The Mediating Role Of Emotional Labor On the Relationship Between Cultural Intelligence And Individual Job Performancementioning
confidence: 99%
“…Also, its relationship with premises such as personality traits (Ang, Van Dyne & Koh, 2006), cross-cultural experience and orientation (Crowne, 2008;Harrison, 2012;Li, Mobley & Kelly, 2013;Kurpis & Hunter, 2017;Pekerti & Arli, 2017;Schwarzenthal, Juang, Schachner, Van de Vijver & Handrick, 2017) and social intelligence (Depaula, Azzollini, Cosentino & Castillo, 2016) has been studied. According to the findings in the literature, it is shown that cultural intelligence increases the job satisfaction of employees in multinational organizations with cultural diversity and reduces their anxiety levels (Bücker, Furrer, Poutsma & Buyens, 2014;Telli & Zehir, 2016), burnout (Tay, Westman & Chia, 2008) and cynicism (Çalışkan, Ünal, Kalafatoğlu, Üçler & Akün, 2015). On the other hand, it has been observed that cultural intelligence positively affects team performance (Groves & Feyerherm, 2011) and increases both organizational commitment (Eskandarpur, Nazari, Vejdan & Tohidi, 2013) and job performance (Rose, Ramalu, Uli & Kumar, 2010: 76-85).…”
Section: The Mediating Role Of Emotional Labor On the Relationship Between Cultural Intelligence And Individual Job Performancementioning
confidence: 99%
“…Akademik ortalamaları ölçmek için ise öğrencilerden demografik bilgiler kısmında genel ağırlıklı not ortalamalarını yazmaları istenmiştir. Kullanılan ölçekler farklı boyutlardan oluşmasına rağmen analizler yapılırken ölçekler yazındaki bazı çalışmalarda olduğu gibi (örn; Çalışkan, 2015;Abdullayeva, 2018, ) toplu olarak kullanılmıştır.…”
Section: Veri Toplama Aracıunclassified